iMENA - Learning from the Innovation Policy Experience in Eastern Europe, Korea and Turkey - Kacem, Rimal (World Bank, Washington, DC, 2013)
Innovation is often touted as a key component in unleashing private sector growth and the dynamism necessary for solving the Middle East and North Africa (MENA) region's employment challenges. The region's innovation strategy identifies the major development challenges including youth unemployment, low diversification of exports, low share of medium and high tech exports, and the need to move from privilege to competition. The MENA region does not perform well on innovation and education indicators, and scores below the world average on the knowledge index (2011). Innovation policies should first focus on improving the business environment, innovation finance, and skills. While developing the innovation policy framework, it will be important to leverage international linkages and to focus on promoting inclusive innovation. MENA's innovation policy agenda will be country specific and difficult to operationalize.